Heightened autoantibody immune response to citrullinated calreticulin in bronchiectasis: Implications for rheumatoid arthritis. (August 2017) - Clarke, Alex; Perry, Elizabeth; Kelly, Clive; De Soyza, Anthony; Heesom, Kate; Gold, Leslie I.; Ollier, William; Hutchinson, David; Eggleton, P.
Graphical abstract: Abstract: Calreticulin (CRT) and citrullinated (citCRT) are implicated in rheumatoid arthritis (RA) pathology. citCRT binds to RA shared epitopes (SE) on HLA-DR molecules with high affinity and triggers pro-inflammatory events in adjacent cells. The aim of the study was to detect the presence of citCRT prior to developing RA and evaluate if citCT is a target for autoantibodies in RA cohorts with and without lung disease. Antibodies were assessed by ELISA against native CRT, citCRT and general protein citrullination, in sera from 50 RA patients without lung disease, 122 bronchiectasis (BR) patients, 52 bronchiectasis patients with RA (BRRA), 87 asthma patients and 77 healthy controls (HC). Serum citCRT was detected by immunoblotting and mass spectrometry. Genomic DNA was genotyped for HLA-DRB1 alleles. Patients were assessed for DAS28, rheumatoid factor, and anti-cyclic citrullinated peptide antibodies. Extracellular citCRT was detected in BR patients sera prior to them developing RA. A citCRT SE binding peptide GEWKPR261cit QIDNPDYK was identified. Anti-CRT antibodies were observed in 18% of BR patients with or without RA. Anti-citCRT antibodies were observed in ∼35% of BR or RA patients, increasing to 58% in BRRA patients. In the RA alone patients 7/20 (35%) who were negative for RF and anti-CCP were anti-CRT antibody positive and had higher DAS28 scores than triple negative RA alone patients. Three of the four BR patients who developed RA over 18 months were anti-citCRT + ve SE +ve . The detection of citCRT in BR and development of anti-citCRT in BR patients suggests citCRT antigens are early targets of antigenicity in these patients, especially in SE +ve patients prior to the onset of RA.